GRAIN SCALE DEFORMATION IN ULTRA-HIGH-PRESSURE METAMORPHIC ROCKS - AN INDICATOR OF RAPID PHASE TRANSFORMATION - Lenze A.; Stöckhert B.; Wirth R. (My University, 2005)
Conspicuous grain scale deformation is observed in some ultra-high-pressure (UHP) metamorphic rocks of the Dora Maira Massif, Western Alps, although no significant strain is discernible on the mesoscopic scale. In a jadeite–kyanite–quartz rock, some of the jadeite crystals reveal (100) deformation twins, indicating local differential stress levels above 0.3 GPa. Many kyanite crystals show marked kink or deformation bands, with a slip system (100)[001]. In contrast, the adjacent coarse-grained quartz matrix (grain size ca. 0.2 mm), which has formed from coesite during exhumation from >100 km depth, reveals a foam structure. The quartz grain boundary configuration is controlled by interfacial free energy, the grains are optically strain-free, and there is no crystallographic preferred orientation. Preservation of this foam microstructure, which indicates grain growth during low-stress annealing, precludes that deformation of the jadeite and kyanite crystals is a result of a late-stage low-temperature overprint. The orientation distribution of jadeite and kyanite with and without twins or deformation bands, respectively, has been investigated with a combination of universal stage and EBSD techniques. On the scale of a thin section, there is no preferred orientation of twinned jadeite and bent kyanite crystals and undeformed crystals, respectively. Thus, the orientation of the inferred local shortening direction is random. This precludes deformation driven by a homogeneous far field tectonic stress, but suggests an internally controlled stress field which is highly inhomogeneous on the scale of a few grain diameters. Laboratory experiments show that the coesite to quartz transformation proceeds within hours after decompression from 3.0 to 2.7 GPa at 800 °C. The microstructures of incompletely transformed samples indicate that the quartz growing at the expense of coesite undergoes crystal plastic deformation and recrystallizes with a very fine grain size during transformation. In this case, the deformation of quartz is attributed to the volumetric strain ΔV=+10% inherent in the coesite–quartz transformation, which causes a highly inhomogeneous stress field inside the sample related to the progress of the transformation. We propose that a similar process has taken place in the polyphase natural rock during exhumation, with the transient stresses causing mechanical twinning of jadeite and bending or kinking of kyanite. When the transformation had gone to completion, grain growth obliterated the microstructures of the quartz matrix, while the deformed jadeite and kyanite crystals preserved the record of inhomogeneous deformation at high temperatures. The peak differential stresses locally exceeded 0.3 GPa, which indicates very high strain rates and a correspondingly rapid transformation of coesite to quartz, comparable to the laboratory results.